Cell surface-expressed phosphatidylserine as therapeutic target to enhance phagocytosis of apoptotic cells - Schutters, K (Nature Publishing Group, 2013)
Impaired efferocytosis has been shown to be associated with, and even to contribute to progression of, chronic inflammatory diseases such as atherosclerosis. Enhancing efferocytosis has been proposed as strategy to treat diseases involving inflammation. Here we present the strategy to increase ‘eat me' signals on the surface of apoptotic cells by targeting cell surface-expressed phosphatidylserine (PS) with a variant of annexin A5 (Arg-Gly-Asp–annexin A5, RGD–anxA5) that has gained the function to interact with α(v)β(3) receptors of the phagocyte. We describe design and characterization of RGD–anxA5 and show that introduction of RGD transforms anxA5 from an inhibitor into a stimulator of efferocytosis. RGD–anxA5 enhances engulfment of apoptotic cells by phorbol-12-myristate-13-acetate-stimulated THP-1 (human acute monocytic leukemia cell line) cells in vitro and resident peritoneal mouse macrophages in vivo. In addition, RGD–anxA5 augments secretion of interleukin-10 during efferocytosis in vivo, thereby possibly adding to an anti-inflammatory environment. We conclude that targeting cell surface-expressed PS is an attractive strategy for treatment of inflammatory diseases and that the rationally designed RGD–anxA5 is a promising therapeutic agent.